Current state of personal data protection in electronic voting: criteria and indicator for effective implementation - Lubis, Muharman; Kartiwi, Mira; Zulhuda, Sonny (Lembaga Penerbitan dan Publikasi Ilmiah (LPPI), 2018)
The adoption of electronic voting has been done in various countries related to cost and time reduction operationally. On the other hand, recent publication has been informed several issues occurred such as technicality, reliability, security and privacy due to the compromised system were used. In small scale, there are certain group of people who want to exploit the vulnerabilities for their own benefit in the election, while in the greater scale, it can reduce public confidence to entrust the adoption of e-voting system to augment participation rate, to improve the quality of voting and to aid the political right effectively. This paper aims to investigate the characteristic of people demanding the legislative to address the criteria and indicator for effective implementation in electronic voting. By understanding the perception of voters in viewing current electoral regulation are essential to provide some ideas and opinions for better enhancement, either through recommendation and drafting related legislation to cater the needs.